2023
DOI: 10.15421/022310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mineral supplementation on qualitative beef parameters

T. V. Farionik,
O. S. Yaremchuk,
O. P. Razanova
et al.

Abstract: Correct nutrition with sufficient amount of optimal doses of microelements efficiently supports high levels of beef production and health of the animals throughout the feeding period. In the sphere of beef production, microelements are needed as additional supplements to play an important role in the productivity of cattle and the quality of the products made from them. Providing cattle with a more bioavailable source of deficient microelements could increase the metabolic process of the main nutrients, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The main objective of modern animal farming is achieving maximum productivity through realization of the genetic potential and survival of the populations, decrease in production costs, and production of highquality meat. Studies by Yaremchuk et al (2022) and Farionik et al (2023) confirmed the importance of correcting the animals' diets with mineral premixes for more intensive growth and enhancement of meat quality. One of the key tendencies in the development of poultry farming has been not only continuous improvement of meatiness, but also improvement of the quality characteristics of the produced meat.…”
Section: Discussionmentioning
confidence: 92%
“…The main objective of modern animal farming is achieving maximum productivity through realization of the genetic potential and survival of the populations, decrease in production costs, and production of highquality meat. Studies by Yaremchuk et al (2022) and Farionik et al (2023) confirmed the importance of correcting the animals' diets with mineral premixes for more intensive growth and enhancement of meat quality. One of the key tendencies in the development of poultry farming has been not only continuous improvement of meatiness, but also improvement of the quality characteristics of the produced meat.…”
Section: Discussionmentioning
confidence: 92%
“…The live weight of broiler chickens on day 8 in all three groups was almost the same at 230.2-239.5 g. Over the next week, after the introduction of the additives under study into the diet, the poultry began to grow more intensively and in the second group the live weight of chickens was 97% higher (at p<0.001), in the third group -by 10.5%. The absolute increase in live weight during the period of feeding the starter feed (days [3][4][5][6][7][8][9][10][11][12][13][14][15] was 11.7% higher in the second group (p<0.01), and 12.7% higher in the third group (p<0.001) compared to the data in the control group. The relative increase in live weight, which characterises the growth rate, during this period of poultry rearing with the introduction of the additive "Kronocid-L" to the diet is 3.3 p.p.…”
Section: Resultsmentioning
confidence: 99%
“…Among the biologically active compounds, those preferred are compounds of natural origin, including mineral. Analysis of the literature indicates that animal nutrition uses a large amount of mineral feed supplements (Surai, 2002;Razanova, 2022;Farionik et al, 2023). Mineral components of the diet play an important role in the metabolic processes of the cells, regulate homeostasis, acid-base homeostasis, and osmotic pressure.…”
Section: Introductionmentioning
confidence: 99%